Policy for Country Contributions for Capacity Building. (Policy Papers; Policy Paper ;, 2008)
This paper proposes a strengthened country contributions policy for capacity-building services. It builds on the recent Executive Board discussions on capacity-building reforms, which included proposals for the use of charges (country contributions) to improve the effectiveness and efficiency of the Fund's capacity-building activities. On the basis of this country contributions policy, management intends to issue a staff guidance note on implementation and to take steps to bring it to the attention of members and other recipients of Fund capacity-building activities.a.